Students' Proportional Reasoning Level in Solving Missing Value Problems with GeoGebra Assistance - Taszkia Aulia Putri; Rooselyna Ekawati; Yurizka Melia Sari (Universitas Negeri Surabaya, 2025)
Proportional reasoning is the basis for understanding advanced mathematical concepts, but students in Indonesia still have difficulty in solving problems involving proportions and ratios. This study aims to describe the level of students' proportional reasoning in solving missing value problems with the help of GeoGebra. The research method used was qualitative with a case study approach, involving three students in class IX at one of the public junior high schools in Surabaya. The selection of subjects was based on mathematical ability, the same gender, and good communication skills. The research instruments included the researcher, mathematics ability test, proportional reasoning test, and interview. The results showed that students with high, medium, and low mathematics ability had reached level 2 in solving missing value problems using GeoGebra. The significant difference among the three students lies in the strategy used when solving the problem. This research has implications for students' proportional reasoning using GeoGebra. However, the results of this study do not represent the overall level of proportional reasoning of junior high school students.